2016
DOI: 10.1002/adv.21718
|View full text |Cite
|
Sign up to set email alerts
|

Study of Solid Particle Erosion Wear Behavior of Bamboo Fiber Reinforced Polymer Composite with Cenosphere Filler

Abstract: In this study, solid particle erosion (SPE) wear behavior of bamboo fiber‐reinforced epoxy composite with cenosphere filler was investigated. Cenosphere is an industrial waste of thermal power plants which is produced during burning of pulverized coals. The present composites consisting of varying weight percentage of fibers and cenosphere fillers were prepared by hand lay‐up technique. The erosion wear rates of these composites have been studied with varying impact velocities and impingement angles. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 43 publications
1
22
0
1
Order By: Relevance
“…Jena et al researched the erosion wear conduct of bamboo fiber‐reinforced polymer composite with cenosphere filler using solid particles as erodent. From their study, they concluded that with the cenosphere filler addition, the erosion wear is reduced and the maximum erosion wear occurs at 60° impingement angle.…”
Section: Introductionmentioning
confidence: 99%
“…Jena et al researched the erosion wear conduct of bamboo fiber‐reinforced polymer composite with cenosphere filler using solid particles as erodent. From their study, they concluded that with the cenosphere filler addition, the erosion wear is reduced and the maximum erosion wear occurs at 60° impingement angle.…”
Section: Introductionmentioning
confidence: 99%
“…There is very less research that has been done so far on the erosive wear in case of natural fiber‐reinforced polymer composites . From the past research work, it is found that none of the research work related to erosive wear analysis of bagasse fiber‐reinforced epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
“…Composites made of polyetherimide and polyphenylenesulfide were studied and erosive wear of the material depends on angle of impingement and velocity (Patel et al, 2018;Tewari et al, 2003;Arjula et al, 2008;Bera et al, 2017;Sarı and Sınmazçelik, 2007). Most of the researchers mentioned the erosive wear of synthetic fibre polymer composites are due to micro-ploughing and micro-cutting during lower erodent velocities, and for higher velocities erosion characterised by severe fibre breakage and matrix erosion (Poursaeidi et al, 2017;Harsha and Thakre, 2007;Jena et al, 2018). Patnaik et al (2008aPatnaik et al ( , 2011 reported that ductile and brittle materials exhibits maximum erosion at range of 15°-30° and 90° angle of impingement respectively (Patnaik et al, 2008a(Patnaik et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The wear/erosive wear of the material has been reduced by adding hard particles as filler material in fibre composites (Jena et al, 2018;Annappa et al, 2017;Srivastava and Pawar, 2006). Especially when the platy shape of the filler were best in reinforcement (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%